2021
DOI: 10.2478/hukin-2021-0106
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Movement Tempo Distribution on Bar Velocity During a Multi-Set Bench Press Exercise

Abstract: The goal of the present study was to evaluate the effect of contrast tempo movement on bar velocity changes during a multi-set bench press exercise. In randomized and counter-balanced order, participants performed three sets of the bench press exercise at 60%1RM under two testing conditions: E-E where all repetitions were performed with explosive (X/0/X/0) movement tempo; and S-E where the first two repetitions were performed with a slow tempo (5/0/X/0) while the third repetition was performed with explosive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…However, the effect size was larger after unilateral training in each variable tested. It is worth referring to the work of Wilk et al [62], which pointed out that the most appropriate TUT for strength gains is between 2 and 20 s per set, while Vieira et al [63] concluded that RT performed not until failure may induce comparable or even greater improvements in maximal dynamic strength and power output. He pointed out that the completion of a maximum concentric repetition of resistance exercises at a particular load could result in greater improvement of maximum strength and power than a relatively slow repetition at a slower tempo with fewer repetitions [64].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect size was larger after unilateral training in each variable tested. It is worth referring to the work of Wilk et al [62], which pointed out that the most appropriate TUT for strength gains is between 2 and 20 s per set, while Vieira et al [63] concluded that RT performed not until failure may induce comparable or even greater improvements in maximal dynamic strength and power output. He pointed out that the completion of a maximum concentric repetition of resistance exercises at a particular load could result in greater improvement of maximum strength and power than a relatively slow repetition at a slower tempo with fewer repetitions [64].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance training (RT) with a different movement tempo (unintentional and intentional) can induce significant changes in muscle strength and power by altering the duration of certain phases of RT ( Wilk et al, 2018 ). An unintentional slow tempo results from a heavy load or fatigue (i.e., increased repetition duration), while an intentional slow movement tempo could be purposefully used with light loads, and when fatigue does not influence one’s ability to control movement velocity ( Trybulski et al, 2021 ; Wilk et al, 2021 ). For instance, 3/1/2/0 represents a 3-s eccentric contraction, a 1-s isometric contraction, a 2-s concentric contraction, with no pauses between each repetition.…”
Section: Introductionmentioning
confidence: 99%